Sarufi ya kiswahili : uchanganuzi na matumizi - Njogu, Kimani; Mwihaki, Alice; Buliba, Aswani (Nairobi, Kenya : Jomo Kenyatta Foundation, 2006)
On analysis and usage of Swahili grammar.
Includes bibliographical references (p. 148-150).
In Swahili.
Keywords: Swahili language -- Grammar